UTILIZATION OF KERNEL OIL LOSSES (PALM KERNEL OIL) AS ROW MATERIAL FOR MAKING SOLID BATH SOAP - Melki Edo Sinabang; Hasan Basri Daulay; Bosman Sidebang; Devi Silsia (BPFP Faperta UNIB, 2021)
Processing of palm kernels at the kernel station of the palm oil mill still has a loss of kernel oil in the bulk silo kernel. This oil can be used as a raw material for solid soap. This study aims to determine the characteristics of solid soap resulting from core oil losses in terms of physical, chemical and organoleptic parameters and to obtain the right concentration of NaOH and fragrance oil volume to produce solid soap according to SNI 06-3532-2016. This study used a completely randomized design (CRD) with 2 factors, namely the concentration of NaOH and the amount of fragrance oil. The variables observed were water content test, foam stability, free alkaline content, pH level, and organoleptic test. Solid soap characteristics are : moisture content 10.22% - 39.17%, foam stability 45.93% - 69.4%, free alkaline content 0.16% - 0.42%, pH 9 , 86 - 13,31. Panelist acceptance rates for texture 3 - 4.05, color 3.3 - 4.05, aroma 3.1 - 3, 85 and oerall 3.35 - 4, 05.Soaps made with 20% NaOH and 2 ml fragrance oil has met SNI 06-3532-2016